Relationship between body mass index (BMI) and oral health status among government bus drivers of Belagavi, India: A cross-sectional study - Mehul A. Shah; Roopali M. Sankeshwari; Anil V. Ankola; Ram Surath Kumar; Varkey Nadakkavukaran Santhosh; Atrey J. Pai Khot; Anu Sara Varghese (Clinical Epidemiology and Global Health, 2023)
Background: Transport workers have a haphazard and incongruent schedule which makes it difficult for them to follow proper oral hygiene practices. Bus drivers whose lifestyle is primarily sedentary and characterized by poor eating habits are at increased risk. This study aimed to investigate the association between BMI and oral health status among NWKRTC (North West Karnataka Road Transport Corporation) bus drivers in Belagavi, India. Methods: A self-designed validated questionnaire was employed to assess oral hygiene status and record soft tissue variations among the bus drivers. A sample size of 300 was recruited for the study using the convenience sampling technique. Descriptive statistics, Chi-square, Kruskal Wallis test, Spearman's correlation, and logistic regression analysis were used for statistical analyses. Results: The mean age of the participants was 42.47 ± 8.44 years. The mean BMI score was found to be 25.43 ± 3.51. The prevalence of dental caries and periodontal disease was found to be 82.7% and 67.6%, respectively. Hypertension (15.67%), diabetes mellitus (14.33%), leukoplakia (8.33%), and OSMF (3.33%) were prevalent and statistically significant (P ≤ 0.05). A positive linear correlation and a significant relationship was found between Decayed, Missing, Filled teeth (DMFT) score (r = +0.44) and Community Periodontal Index (CPI) score (r = +0.17) with BMI. Participants with dental caries (aOR:1.20; 95%CI: 0.55–2.61) and periodontal disease BMI (aOR:1.91; 95%CI:1.19–3.06) exhibited increased odds of having higher BMI. Conclusion: The study revealed a significant association between BMI and both oral health status and systemic conditions among government bus drivers in Belagavi.